Minat Berwirausaha Kaum Wanita di Kota Purwokerto - Nirmala Nirmala; Wisnu Wijayanto (Ekonomis: Journal of Economics and Business, 2021)
This study aims to identify the factors that encourage women's interest in entrepreneurship. This research uses a qualitative approach. Data collection techniques were carried out through observation, in-depth interviews, and discussions. Based on the sampling technique using purposive sampling method and snowball sampling, it obtained 30 respondents. Data analysis using data analysis model Miles and Huberman. The results showed that (1) as many as 56.7% of women entrepreneurs who have run their businesses for more than 3 years, (2) as many as 80% of women entrepreneurs are engaged in the culinary field, (3) as many as 30% of informants got the initial idea to open a business to distribute hobbies, as well as (4) factors that encourage women's interest in entrepreneurship are seeing business opportunities as much as 40%, the desire to improve self-efficacy by 23.4%, having flexibility in time and opening employment opportunities as much as 13.3%, and the desire to manage finances itself as much as 10%. The implications of this research are (1) business owners need a strong entrepreneurial spirit and commitment in running a business as one of the keys to success in developing a business (2) people who want to be entrepreneurial can increase their discernment to see and seize business opportunities, (3) the government, especially government agencies. related needs to be more active in empowering and fostering women entrepreneurs, especially in terms of business management capabilities.